Analisis Kesesuaian Program dengan Kelompok Sasaran pada Pengembangan UMKM di Kabupaten Sidoarjo - Muhammad Arfi Rayyan (Journal of Governance and Administrative Reform, 2020)
Abstract This study aims to describe the suitability of the program with the target group in the development of MSMEs in Sidoarjo Regency, the Tukuo digital marketplace platform as an effort to increase marketing. The theory used is the theory of program implementation or better known as the three way fit proposed by David C. Korten. This study uses a qualitative approach with a descriptive type of research. The location of the research was carried out in Sidoarjo Regency. Determination of informants was carried out using purposive techniques and also snowball techniques. The data collection process was carried out using direct and indirect interview techniques, as well as observation, audio and visual documentation together with selected informants, namely government structural officials and with informants from the results of the snowball sampling technique on government staff and SMEs assisted by Sidoarjo who have a connection with Tukuo digital marketplace platform. Data analysis used qualitative analysis with stages, data reduction, data presentation, and conclusion drawing. The results show that the Tukuo platform that has been implemented does not yet have a sufficiently mature compatibility. The suitability of the implementing organization in running the Tukuo platform has also not been fully achieved.. Keywords: MSME development, digital marketing Abstrak Penelitian ini bertujuan mendiskripsikan kesesuaian program dengan kelompok sasaran pada pengembangan UMKM di Kabupaten Sidoarjo platform digital marketplace tukuo sebagai upaya peningkatan pemasaran. Teori yang digunakan adalah teori implementasi program atau lebih dikenal dengan three way fit yang dikemukakan oleh David C. Korten. Penelitian ini menggunakan pendekatan kualitatif dengan tipe penelitian deskriptif. Lokasi penelitian dilaksanakan di Kabupaten Sidoarjo. Penetapan informan dilakukan dengan menggunakan teknik purposive dan juga teknik snowball. Proses pengambilan data dilakukan menggunakan teknik wawancara secara langsung dan tidak langsung, serta observasi, dokumentasi audio dan visual bersama dengan informan yang dipilih yaitu pejabat struktural pemerintahan serta dengan informan dari hasil teknik snowball sampling terhadap staf bagian pemerintahan dan pelaku UKM Binaan Sidoarjo yang memiliki keterkatian dengan platform digital marketplace tukuo. Analisis data menggunakan analisis kualitatif dengan tahapan, reduksi data, penyajian data, penarikan kesimpulan. Hasil penelitian menunjukkan bahwa platform Tukuo yang telah diimplementasikan belum memiliki kesesuaian yang cukup matang. Kesesuaian organisasi pelaksana dalam menjalankan platform Tukuo juga belum sepenuhnya tercapai. Kata kunci: pengembangan UMKM, pemasaran digital